2021
DOI: 10.1111/jon.12907
|View full text |Cite
|
Sign up to set email alerts
|

Nerve ultrasound findings in Sjögren's syndrome‐associated neuropathy

Abstract: Background and Purpose:The phenotype of Sjögren's syndrome-associated neuropathy has been better characterized in recent years. However, Sjögren's syndrome-associated neuropathy remains an underdiagnosed entity with only few insights considering the pathomechanisms of nerve damage. Nerve ultrasound has proven to be a useful and efficient tool in detecting nerve damage of autoimmune origin. We, therefore, aimed to evaluate this method for Sjögren's syndrome-associated neuropathy. Methods:Patients with Sjögren's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…These patients have been shown to have different clinical and paraclinical features compared with patients with SS without neurological involvement [ 3 , 25 ]. Patients with SS-associated polyneuropathy showed pathological results not only in nerve conduction, but also in ultrasound examinations of the nerves, and often meet the diagnostic criteria for CIDP [ 4 , 25 ]. However, compared with patients with CIDP and without SS, a higher frequency of women and cranial nerve affection has been reported [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These patients have been shown to have different clinical and paraclinical features compared with patients with SS without neurological involvement [ 3 , 25 ]. Patients with SS-associated polyneuropathy showed pathological results not only in nerve conduction, but also in ultrasound examinations of the nerves, and often meet the diagnostic criteria for CIDP [ 4 , 25 ]. However, compared with patients with CIDP and without SS, a higher frequency of women and cranial nerve affection has been reported [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sjögren´s syndrome (SS) is an autoimmune disease characterized by lymphocytic infiltration of the exocrine glands leading to sicca symptoms, but may also cause extra-glandular manifestations such as interstitial lung disease, arthritis, cutaneous vasculitis, and central or peripheral nervous system (CNS and PNS) involvement [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. According to the latest American College of Rheumatology/European League Against Rheumatism (ACR/EULAR) classification criteria of 2016, SS can be diagnosed in a patient with sicca symptoms and additional anti-SSA(Ro)-antibody positivity and/or pathological focus scores on a minor salivary gland biopsy [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the clinical score of the dry eye and the Ocular Surface Disease Index, there were no significant in-between-group differences between patients with Neuro-Sjögren and CIDP. Nevertheless, controls reached significantly better results at the clinical score of the dry eye when compared with the Neuro-Sjögren group (values are stated as median (interquartile range)): Neuro-Sjögren group 6 (4-8) (left) and 6 (4)(5)(6)(7)(8) [right]; CIDP group 4 (3-5) (left, p = 0.12) and 4 (3-6) (right, p = 0.12); controls 1 (0-3) (left, p = 0.003) and 2 (1-3) (right, p = 0.003).…”
Section: Clinical Evaluation Of Dry Eye Symptoms and Signsmentioning
confidence: 99%
“…Previous studies have found many similarities between the neuropathy associated with Sjögren’s syndrome and other autoimmune-mediated neuropathies such as chronic inflammatory demyelinating polyneuropathy. Both entities are associated with, for example, focal thickening of peripheral nerves and/or prominent fascicles [ 8 ]. In a comparison of CIDP patients with and without Sjögren’s syndrome, only cranial nerve impairment and female sex were more common in the subgroup with additional Sjögren’s syndrome, while clinical presentation as well as electrophysiological and laboratory findings of cerebrospinal fluid were similar [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the inherent heterogeneity of such cohorts, such as the heterogeneous group of patients with pSS and varying manifestations, this finding is perhaps unsurprising ( 11 , 12 ). The aim of this study is to independently assess the role of SGUS in a large, unselected Sicca syndrome cohort that has undergone extended-criteria phenotypic clustering.…”
Section: Introductionmentioning
confidence: 99%